Anaphylaxis in elderly people. Issue 6 (14th December 2022) - Ventura, Maria Teresa; Boni, Elisa; Taborda-Barata, Luis; Blain, Hubert; Bousquet, Jean
Abstract : Purpose of review: Anaphylaxis is common in old-age adults but is insufficiently understood by physicians, and may be underdiagnosed. This review discusses the specificities of anaphylaxis in this age group and stresses the importance of adrenaline in its management. Recent findings: Data from the European Anaphylaxis Registry on elderly patients is a major finding. Other findings include the prevention of possible anaphylactic reactions in coronavirus disease 2019 vaccination as well as some new epidemiologic data. Summary: The most common risk factors are hymenoptera venom and food and drug allergy. Cardiovascular symptoms are the most important ones to reverse in old-age adults, especially due to the multiple comorbidities. Anaphylaxis in old-age adults has a more severe outcome than in younger ones. Polypharmacy is a specific factor to be considered. The Airway, Breathing, Circulation, Disability, Exposure (ABCDE) algorithm is applicable in all clinical emergencies for immediate assessment and treatment, and should be considered for all patients. Adrenaline is the mainstay of the management of the condition. There are no absolute contraindications to the prescription of self-injectable adrenaline in elderly individuals at risk of anaphylaxis.